2012
DOI: 10.1038/nrendo.2011.224
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Müllerian hormone: an ovarian reserve marker in primary ovarian insufficiency

Abstract: Primary ovarian insufficiency (POI), also known as premature ovarian failure, is a disorder of infertility characterized by amenorrhoea, low estrogen levels and increased gonadotropin levels in women aged <40 years. POI is the result of premature exhaustion of the follicle pool or can be attributed to follicular dysfunction, for example, owing to mutations in the follicle-stimulating hormone receptor or steroidogenic cell autoimmunity. Moreover, advances in cancer therapeutics over the past decades have led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
162
0
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(172 citation statements)
references
References 136 publications
4
162
0
6
Order By: Relevance
“…The number and state of the germ cells in the gonads is the major determinant of the level of AMH in the circulation. This is most clearly established for females (Visser et al 2012), but it may also be the case for males, as germ cells regulate Sertoli cells (O'Shaughnessy et al 2008, Cool et al 2012, Dabaja et al 2015. Consequently, AMH is uniquely and ideally placed to convey information about the current and future reproductive capacity of an individual.…”
Section: Circulatory Amh May Signal Reproductive Status In Adultsmentioning
confidence: 99%
“…The number and state of the germ cells in the gonads is the major determinant of the level of AMH in the circulation. This is most clearly established for females (Visser et al 2012), but it may also be the case for males, as germ cells regulate Sertoli cells (O'Shaughnessy et al 2008, Cool et al 2012, Dabaja et al 2015. Consequently, AMH is uniquely and ideally placed to convey information about the current and future reproductive capacity of an individual.…”
Section: Circulatory Amh May Signal Reproductive Status In Adultsmentioning
confidence: 99%
“…Therefore, similar to the prediction of menopause onset, serum AMH has been considered as a possible marker for identifying women with diminished ovarian reserve who are likely to develop POI. Several studies have shown that serum AMH levels are much lower in women with symptomatic ovarian insufficiency [50][51][52][53]. In an era in which it is possible to maintain fertility via cryopreservation of ovaries and/or oocytes, these trials seem to be meaningful for the presupposition of accurate prediction.…”
Section: Prediction Of Menopause/primary Ovarian Insufficiency (Poi)mentioning
confidence: 99%
“…It is characterized by primary or secondary amenorrhea for at least 4 months in women under the age of 40, menopausal serum FSH levels (above 40 IU/L) obtained on two occasions at least 1 month apart and low estradiol levels (below 50 pg/mL) [1]. Another indicator is the antiMüllerian hormone (AMH), whose serum levels can help assess the state of follicular senescence, which is a possible predictor of risk for POI [2]. However, there are presently no single screening tests that can predict a woman's reproductive lifespan [3].…”
Section: Introductionmentioning
confidence: 99%